Implementasi Akuntabilitas dalam Shari’ah Enterprise Theory di Lembaga Bisnis Syari’ah (Studi Kasus: Swalayan Pamella Yogyakarta) - Rahmah Yulisa Kalbarini (Al-Tijary, 2018)
This study aimed to find out accountability within Shari’ah Enterprise Theory and know the process also the type of accountability in islamic business organization case study at Pamella Supermarket. The method of this study was qualitative approach using research study. The analyze technique is domain and taxonomy. The results obtained, that the implementation of accountability with Shari’ah Enterprise Theory in Pamella Supermarket based on pamella owner’s concept on accountability that the purpose of life is rahmatan lil alamin that is each muslim can give a benefit to of the muslims. The realization of that concept is there will be a separation of responsibility: business fund from social fund which is managed by Pamella. From the supermarket sight, the business fund is under the responsibility of the owner and to Allah SWT. While the social fund is under the responsibilityof the society by holding some social humanity program, which are reported to the society as well as to the existing interrelated departments in Yogyakarta